2018
DOI: 10.1080/01616412.2018.1446282
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Evans blue clearance from cerebrospinal fluid into meningeal lymphatic vessels and deep cervical lymph nodes

Abstract: Objectives Recently, it has been confirmed, that excess fluid and waste products from the brain are drained into the cerebrospinal fluid (CSF) and afterwards cleared via the olfactory route and/or lymphatic vessels in the brain dura and corresponding extracranial lymphatic structures. Therefore, the aim of present study was to monitor time-dependent uptake of Evans blue (EB) tracer from subarachnoid space into the meningeal lymphatic vessels and extracranial lymph nodes in rats during 3 hours-12 days. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 20 publications
1
30
0
1
Order By: Relevance
“…Experiments to elucidate physiological CSF dynamics are challenging and often involve some sort of intervention. In this study, we infused the CSF tracer, Evans blue, directly into the lateral ventricles of the animals [18,21,22]. This type of intervention has the potential to disturb normal CSF dynamics; however, this technique is widely used and we took care to limit the infusion rate to lower than that of CSF production (2.66-2.84 µl/min) to maintain the integrity of the system as much as possible [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments to elucidate physiological CSF dynamics are challenging and often involve some sort of intervention. In this study, we infused the CSF tracer, Evans blue, directly into the lateral ventricles of the animals [18,21,22]. This type of intervention has the potential to disturb normal CSF dynamics; however, this technique is widely used and we took care to limit the infusion rate to lower than that of CSF production (2.66-2.84 µl/min) to maintain the integrity of the system as much as possible [23].…”
Section: Discussionmentioning
confidence: 99%
“…Several CSF drainage hypotheses have been presented in recent years and we are yet to meet a consensus on the topic [24][25][26]. In recent years, lymphatic drainage of CSF from both the cranium and the spinal space have gained merit in the eld, with several groups demonstrating the presence of CSF tracers in the peripheral lymphatic system, primarily the cervical lymphatics [21,[27][28][29][30]. This may be an interesting direction of investigation to understand how CSF drainage is altered post-stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, using the dye EB as tool, we demonstrated the dermal-trigeminal-brain perivascular spaces or tissues were main pathways for intradermal brain-targeted delivery, and the lymphatic network linked to perivascular spaces or tissues. EB was extensively used as lymphatic vessels tracer in CSF drainage and the BBB permeability; in addition, EB binds to extracellular matrix, such as collagen, elastin and AMPA receptors (Heinle and Lindner, 1984; Weiser et al., 1996; Marchi et al., 2010; Maloveska et al., 2018). It is easy to visualize the structures or tissues and the lymphatic vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The dermal-trigeminal-CNS lymphatic systems might connect to the perivascular spaces or tissues. In the CNS, dural lymphatic vessels, perivascular spaces, and parenchymal paravascular microcirculation function as exchange channels, and the dural lymphatic vessels connected the perivascular spaces and the extra-cranial lymphatic systems (Durant and Yaksh, 1986; Iliff and Nedergaard, 2013; Rangroo Thrane et al., 2013; Aspelund et al., 2015; Maloveska et al., 2018). The trigeminal perineurium and the epineurium elongate from pia and dura mater, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Maloveska и соавт. обнаружили, что краситель Evans blue, введенный в большую цистерну, в течение 3 часов -12 дней дренируется через менингеальные лимфатические сосуды в направлении экстракраниальной дренажной системы, в частности в глубокие шейные лимфоузлы [50]. В работе [51] продемонстрировано, что менингеальные лимфатические сосуды ответственны за дренирование макромолекул и иммунных клеток из ЦСЖ при нейровоспалительных состояниях, а менингеальные лимфатические узлы управляют воспалительными процессами и иммунным наблюдением за ЦНС.…”
Section: визуализация глимфатической системыunclassified